Implementation and Obstacles of The Third Dosage COVID-19 Vaccination Program in Lampung Province in 2022 - Apreh Ristanasari; Wiku Bakti Bawono Adisasmito (Journal of Social Science, 2023)
The high number of cases and deaths due to COVID-19 has caused a number of countries, including Indonesia, to continue to struggle to stop its spread. In addition to carrying out health protocols, it is necessary to carry out vaccinations. The COVID-19 vaccine has proven to be quite safe and effective and shows high protection against infection, hospitalization and death from the virus. However, the efficacy or effectiveness against viral infections decreases after six months, so a booster vaccine is needed. Coverage of the third dose of the covid-19 vaccine in Indonesia is still low at 28.39%. Lampung Province is one of the provinces that has a low coverage of 26.96%. In addition, Lampung Province is a province with a high risk when viewed from the CFR COVID-19 figure of 5.59%. The purpose of this study was to describe the implementation of the third dose of COVID-19 vaccination in Lampung Province and identify the obstacles that occurred in its. This research is a qualitative research with a descriptive approach. Data collection techniques used in-depth interviews and document review. The research results show the availability of policies that support implementation, there is a regional role in funding, a lack of human resources, infrastructure as well as tools and materials. There are obstacles to the process of implementing, recording and reporting and the low coverage of the third dose of the COVID-19 vaccine. The implementation of the third dose of Covid-19 vaccination in Lampung Province is still not optimal and there are still obstacles in its implementation that affect program coverage. Barriers that occur are internal (service provider) and external (service recipient) barriers.